Differences In Fasting Blood Glucose Levels In Acceptors Progestin Injections And Combination Injections - Siti Cholifah; Paramitha Amelia Kusumawardani; Miftahul Muslih (Alma Ata University Press, 2020)
Efforts to limit and regulate birth spacing as a goal to create quality families and healthy families, the government encourages people to use contraceptives as birth control. One of these contraceptives is injection contraception. Injecting contraception is the most widely used contraceptive tool by the people of Indonesia, is considered effective, practical, but has several side effects, the most worrying is that it affects blood glucose. Blood glucose levels in the human body that increase more than normal can be a symptom of diabetes mellitus. The purpose of this study is to determine differences in blood glucose levels in progestin injection and combined injection contraceptive acceptors. Observational research design using a cross sectional approach. The study population was all injectable acceptors. Samples were taken that met the inclusion criteria, namely respondents were willing to be examined, there was no history of diabetes mellitus (DM), less than 40 years of age, acceptors of at least 6-8 hours fasting. Sampling was carried out using consecutive sampling techniques totaling 50 acceptors (25 progestin injection acceptors, 25 combined injection acceptors). Data were analyzed by Witney mann test using α = 0.05. The results showed the mean fasting blood glucose for progestin injection acceptors was higher than for combination injections, the test results P = 0.008 <α = 0.05. The conclusions of the study show that there are significant differences in blood glucose levels in progestin-injecting acceptors and this combination means that progestin-injecting contraceptives have a higher impact on increasing fasting blood sugar levels compared with combined injection contraception. Suggestions for health workers to control blood glucose injector acceptors at acceptors who experience high glucose levels are recommended to replace non-hormonal contraceptive methods.